Numerical simulation of internal and near-nozzle flow of a gasoline direct injection fuel injector. (November 2015) - Saha, Kaushik; Som, Sibendu; Battistoni, Michele; Li, Yanheng; Quan, Shaoping; Senecal, Peter Kelly
Abstract: A numerical study of two-phase flow inside the nozzle holes and the issuing spray jets for a multi-hole direct injection gasoline injector has been presented in this work. The injector geometry is representative of the Spray G nozzle, an eight-hole counterbore injector, from, the Engine Combustion Network (ECN). Simulations have been carried out for the fixed needle lift. Effects of turbulence, compressibility and, non-condensable gases have been considered in this work. Standard k—ɛ turbulence model has been used to model the turbulence. Homogeneous Relaxation Model (HRM) coupled with Volume of Fluid (VOF) approach has been utilized to capture the phase change phenomena inside and outside the injector nozzle. Three different boundary conditions for the outlet domain have been imposed to examine non-flashing and evaporative, non-flashing and non-evaporative, and flashing conditions. Inside the nozzle holes mild cavitation-like and in the near-nozzle region flash boiling phenomena have been predicted in this study when liquid fuel is subjected to superheated ambiance. Noticeable hole to hole variation has been also observed in terms of mass flow rates for all the holes under both flashing and non-flashing conditions.